Analisis Laporan Keuangan Dar, Der Dan Lder Pada Pt Astra Internasional Tbk - Maksum, Maksum; Yuliana, Yuliana (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2024)
Financial reports are records of a company's financial information during an accounting period that can be used to describe the company's performance. The aim of this research is to find out how big the Debt to Asset Ratio, Debt to Equity Ratio and Time Interest Earned Ratio are at PT Astra Internasional Tbk for the 2019-2023 period. The tool used is financial ratios. In this research, researchers used quantitative data, namely in the form of financial reports at PT Astra Internasional Tbk. The research method used is a descriptive research method, namely a technique or method used by researchers to describe the actual subject and object. This research uses a single variable, with aspects of Debt to Asset Ratio, Debt to Equity Ratio and Long Term Debt to Equity Ratio. The results of this research show that the Debt to Asset Ratio level at PT Astra Internasional Tbk is said to be bad because it exceeds industry standards. On the other hand, the Debt to Equity Ratio is said to be good because it is below the existing industry standard average, while the Long Term Debt to Equity Ratio is said to be bad because it is above the industry standard.